Contradictions Neuroscience and Religion - Musacchio, José M. (Springer Praxis Books, 2012)
"Contradictions" is a general interest book that exposes the incompatibility between popular religious beliefs and the scientific view of human nature. It begins with a survey of the evolution of religions and their continuing, often irrational, influences in modern society. Then, based on his long experience in neuroscience, the author takes issue with Decartes about the duality of body and soul. He presents case studies of patients with brain diseases and from these deduces that the soul, far from being separate and supernatural, is no more or less than our way of experiencing our brains ... and which correspondingly disintegrates when they do. Convincing clinical findings and powerful arguments about the universality of truth make this book a bold contribution to the debate about belief and religion in the modern world.